Physiological and Transcriptional Responses of Streptomyces albulus to Acid Stress in the Biosynthesis of ε-Poly-L-lysine - Wang, Chenying; Ren, Xidong; Yu, Chao; Wang, Junming; Wang, Li; Zhuge, Xin; Liu, Xinli (Frontiers in Microbiology, 2020)
Streptomyces albulus has commercially been used for the production of ε-poly-L-lysine (ε-PL), a natural food preservative, where acid stress is inevitably encountered in the biosynthesis process. To elucidate the acid tolerance response (ATR), a comparative physiology and transcriptomic analysis of S. albulus M-Z18 at different environmental pH (5.0, 4.0 and 3.0) was carried out. In response to acid stress, cell envelope regulated the membrane fatty acid composition and chain length to reduce damage. Moreover, intracellular pH was maintained homeostasis by increasing H+-ATPase activity and intracellular ATP and amino acid (mainly arginine, glutamate, aspartate and lysine) concentrations. Transcriptional analysis based on RNA-sequencing indicated that acid stress aroused global changes and the differentially expressed genes involved in transcriptional regulation, stress-response protein, transporter, cell envelope, secondary metabolite biosynthesis, DNA and RNA metabolism and ribosome subunit. Consequently, the ATR of S. albulus was preliminarily proposed. Notably, it is indicated that the biosynthesis of ε-PL is also a response mechanism for S. albulus to combat acid stress. These results provide new insights into the ATR of S. albulus and will contribute to the production of ε-PL via adaptive evolution or metabolic engineering.